ANALISIS PERAN IDENTIFIKASI SIDIK JARI DALAM PENGUNGKAPAN PELAKUTINDAK PIDANA - Heni Siswanto (Fiat Justisia: Jurnal Ilmu Hukum, 2007)
The role of fingerprint identification in the disclosure of criminal divided into three stages, namely the initial stage of the investigation as evidence or clues to narrow prejudice and strengthen the confidence members of the police against suspected criminals. At this stage of the investigation as early very strong evidence to prove a person as a criminal suspect can be used against a suspect's alibi and make it as a suspect of a crime he did. At the stage of evidence in court as evidence to convince the expert testimony and be considered judges to provide a court ruling against the defendant. Keywords: Fingerprint, Crime Actors Disclosure